Selected biochemistry topics for high school biology teachers - Reyes, Vicenta (Francisco) 1934- (s.n.], 1968)
The study determined and analyzed the relation between the principal's ideal and observed behaviors, specifically in the dimensions of "consideration" and "initiating structure" of leadership. Results of the study show that principals exhibit to a greater degree the "consideration" dimension than the "initiating structure" dimension, low and negligible relationships exist between ideal and observed leader behaviors, certain duties and responsibilities of the school principal demand the exercise of both dimensions of leadership, and both the superior and subordinate respondent raters agreed that principals are human-relations-oriented rather than task-oriented.